2011
DOI: 10.1093/ndt/gfr253
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 and ABCB1 polymorphisms in donor and recipient: impact on Tacrolimus dose requirements and clinical outcome after renal transplantation

Abstract: Recipient CYP3A5 6986A>G polymorphism explains part of the interindividual variability of the pharmacokinetics of Tacrolimus. The clinical outcome at 2-year follow-up does not appear to be related to the donor or recipient CYP3A5 6986A>G and/or ABCB1 3435C>T polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 12 publications
5
62
3
1
Order By: Relevance
“…This is in accordance with the previous assumption that a constantly high dose of Tac may lead to a worsening of renal function. This finding may be contradictory to the majority of previously published studies, but the majority of them limited their observations at the first year after transplantation (6,31). However, certain authors found an association between Tac toxicity and patient genotype.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This is in accordance with the previous assumption that a constantly high dose of Tac may lead to a worsening of renal function. This finding may be contradictory to the majority of previously published studies, but the majority of them limited their observations at the first year after transplantation (6,31). However, certain authors found an association between Tac toxicity and patient genotype.…”
Section: Discussioncontrasting
confidence: 61%
“…The controversy in the results concerning the long-term adverse effects of Tac prompted an assessment of the contribution of CYP 3A5 and ABCB1 polymorphisms on renal function parameters in transplant recipients in the present study. The majority of the previous studies found no correlation between investigated polymorphisms and the clinical features of Tac toxicity or renal function attenuation (6,8,31). The bivariate linear regression showed that CYP 3A5 polymorphism, but not ABCB1 polymorphism, independently affects renal function from 6 to 24 months after renal transplantation (Table V).…”
Section: Discussionmentioning
confidence: 91%
“…[17] Other investigators have also reported that CYP3A5 expressers do not have a higher risk of developing acute rejection. [18][19][20][21][22][23][24][25][26] Although numerous studies have reported the higher Tac dose requirement of CYP3A5 expressers compared to nonexpressers, the clinical relevance of this association is unclear and has so far only been investigated in two randomized-controlled clinical trials (RCT). The Tactique study [27] was a multicenter RCT, including 280 renal transplant recipients.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…A polymorphism in intron 3 of CYP3A5, the CYP3A5*3 allele, results in a premature stop codon, whereas individuals carrying the CYP3A5*1 allele express this enzyme normally . Several studies have associated the presence of CYP3A5*1 allele with lower doseadjusted tacrolimus blood concentrations and higher tacrolimus dose requirements (Glowacki et al, 2011;Cho et al, 2012). On the other hand, the influence of ABCB1 polymorphisms (gene coding for P glycoprotein) on tacrolimus pharmacokinetics and clinical outcomes is still controversial Glowacki et al, 2011).…”
Section: Introductionmentioning
confidence: 99%